Effect of quantum dispersion on the radial distribution function of a one-component sticky-hard-sphere fluid. (16th April 2018) - Fantoni, Riccardo
Abstract: In this short communication we present a possible scheme to study the radial distribution function of the quantum slightly polydisperse Baxter sticky hard sphere liquid at finite temperature thorugh a semi-analytical method devised by Chandler and Wolynes.